Clinical Characteristics of Refractory Coronavirus Disease 2019 in Wuhan, China. (16th March 2020) - Mo, Pingzheng; Xing, Yuanyuan; Xiao, Yu; Deng, Liping; Zhao, Qiu; Wang, Hongling; Xiong, Yong; Cheng, Zhenshun; Gao, Shicheng; Liang, Ke; Luo, Mingqi; Chen, Tielong; et al.
Abstract: Background: Since December 2019, coronavirus disease 2019 (COVID-19), caused by severe adult respiratory syndrome coronavirus 2, occurred in Wuhan, and rapidly spread throughout China. This study aimed to clarify the characteristics of patients with refractory COVID-19. Methods: In this retrospective single-center study, we included 155 consecutive patients with confirmed COVID-19 in Zhongnan Hospital of Wuhan University from 1 January to 5 February. The cases were divided into general and refractory COVID-19 groups according to the clinical efficacy of treatment after hospitalization, and the differences between groups were compared. Results: Compared with patients with general COVID-19 (45.2%), those with refractory disease were older, were more likely to be male, and had more underlying comorbid conditions, a lower incidence of fever, higher maximum temperatures among patients with fever, higher incidences of shortness of breath and anorexia, more severe disease assessment at admission, higher neutrophil, aspartate aminotransferase, lactate dehydrogenase, and C-reactive protein levels, lower platelet counts and albumin levels, and higher incidences of bilateral pneumonia and pleural effusion ( P < .05). Patients with refractory COVID-19 were more likely to receive oxygen, mechanical ventilation, expectorant, and adjunctive treatment, including corticosteroids, antiviral drugs, and immune enhancers ( P < .05). Considering the factors of disease severity at admission, mechanical ventilation, and intensive care unit transfer, patients with refractory COVID-19 were also more likely to be male, have manifestations of anorexia on admission, and receive oxygen, expectorant, and adjunctive agents ( P < .05). Conclusion: In nearly 50% of patients with COVID-19 obvious clinical and radiological remission was not achieved within 10 days after hospitalization. Male, anorexia, and no fever at admission was predictive of poor treatment efficacy. Abstract : In nearly 50% of patients with coronavirus disease 2019 (COVID-19), obvious clinical and radiological remission could not be attained within 10 days after hospitalization. There were obvious differences in clinical characteristics between patients with refractory versus general COVID-19.